FINANCIAL RESILIENCE IN THE QUARTER-LIFE CRISIS PHASE GROUP: ANALYSIS OF THE ROLES OF FINANCIAL LITERACY, FINANCIAL PLANNING, SELF-EFFICACY AND INCOME - Hendri, Hendri; Usman, Usman (LPPM STIE Muhammadiah Bandung, 2023)
Financial Resilience is the ability to withstand and recover when faced with challenging economic conditions. This study aims to examine the influence of financial literacy, financial planning, self-efficacy, and income on the financial resilience of individuals in the quarter-life crisis phase. The research employed a quantitative approach, and data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. A total of 255 respondents were obtained through purposive sampling and online questionnaires. The research findings conclude that financial literacy and financial planning positively and significantly impact financial resilience. However, self-efficacy and income do not positively influence financial resilience.